1975
DOI: 10.1093/jnci/55.3.597
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic Activity of Cannabinoids2

Abstract: Lewis lung adenocarcinoma growth was retarded by the oral administration of delta9-tetrahydrocannabinol (delta9-THC), delta8-tetrahydrocannabinol (delta8-THC), and cannabinol (CBN), but not cannabidiol (CBD). Animals treated for 10 consecutive days with delta9-THC, beginning the day after tumor implantation, demonstrated a dose-dependent action of retarded tumor growth. Mice treated for 20 consecutive days with delta8-THC and CBN had reduced primary tumor size. CBD showed no inhibitory effect on tumor growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
176
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(180 citation statements)
references
References 7 publications
0
176
0
4
Order By: Relevance
“…Thus far, no studies have been undertaken to assess whether CB1 might serve as a future target for therapeutic intervention in this tumor. Evidence exists since 1975 that cancer cell growth can be inhibited by treatment with cannabinoid receptor agonists, as first described by Munson et al in Lewis lung carcinoma cells (8). Since then, additional cancer cell types such as glioblastoma (9), breast carcinoma (10), or melanoma (11) were reported to be sensitive to the antiproliferative action of cannabinoids.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus far, no studies have been undertaken to assess whether CB1 might serve as a future target for therapeutic intervention in this tumor. Evidence exists since 1975 that cancer cell growth can be inhibited by treatment with cannabinoid receptor agonists, as first described by Munson et al in Lewis lung carcinoma cells (8). Since then, additional cancer cell types such as glioblastoma (9), breast carcinoma (10), or melanoma (11) were reported to be sensitive to the antiproliferative action of cannabinoids.…”
Section: Introductionmentioning
confidence: 98%
“…In general, the antitumoral actions of diverse cannabinoid receptor agonists are mediated through the cannabinoid receptor types CB1 and CB2, as reviewed by Guzman et al (12). Notably, not only in vitro cell culture systems are subject to this treatment response but also in vivo experiments using either xenografts or syngeneic mouse models have shown the potential of cannabinoids as anticancer agents, without observing major psychoactive or immune-suppressive effects (8,13). Recently, the first clinical study using Δ 9 -tetrahydrocannabinol (THC) in severe cases of glioblastoma has been reported (14).…”
Section: Introductionmentioning
confidence: 99%
“…Other potential palliative effects of cannabinoids in oncology -supported by phase III clinical trials -include appetite stimulation and pain inhibition (Guzmán, 2003;Hall et al, 2005). In addition, cannabinoids have been proposed as potential antitumoral agents owing to their ability to inhibit the growth and angiogenesis of various types of tumour xenografts in animal models (Munson et al, 1975;Guzmán, 2003). However, the antitumoral effect of cannabinoids has never been tested in humans.…”
mentioning
confidence: 99%
“…In recent years, there is a renewed interest in the role of cannabinoids in cancer therapy. Antitumoral effects of cannabinoid on various types of tumor xenografts including lung adenocarcinoma [6], glioma [7], and thyroid epithelioma [8] in animal models have been identified.…”
mentioning
confidence: 99%